AB0046 Tofacitinib impairs monocyte-derived dendritic cell differentiation in rheumatoid arthritisand psoriatic arthritis. (12th June 2018) - Marzaioli, V.; Canavan, M.; Wade, S.; Low, C.; Veale, D.J.; Fearon, U.
Abstract : Background: Tofacinitib (Pfizer) is an oral Janus kinase inhibitor, recently approved for the treatment of rheumatoid arthritis (RA). Although its mechanism of action has been explored in circulating cells, in particular neutrophils and lymphocyte, its effect on dendritic cells development remains still to be elucidate. Monocyte-derived dendritic cells are a subset of inflammatory DC derived from circulating monocytes and have a key role in inflammation and infection. Objectives: The aim of this project is to evaluate the effect of Tofacitinib on inflammatory monocyte-derived dendritic cells (Mo-DC) from RA and PsA patients, and in particular on the ability of monocyte to differentiate into dendritic cells, an important step in innate immunity. Methods: Mo-DC were isolated from blood of RA and psoriatic arthritis (PsA) patients by magnetic separation. Monocyte were plated in presence/absence of GM-CSF/IL-4 cocktail for 7 days, to acquire immature dendritic cell phenotype. To evaluate the effect of Tofacinitib on Mo-DC differentiation, monocyte were treated with 1 µM Tofacinitib (or DMSO as control) for 15 min prior to cytokine stimulation. CD209 (immature DC marker) and CD14 (monocyte marker) were evaluated by flow cytometry in the CD11c positive population. Phagocytosis was investigated by the analysis of dendritic cell uptake of soluble antigens through two different mechanisms: non-specific macropinocytosis (using Lucifer Yellow), and receptor-mediated endocytosis (using DQ TM Ovalbumin). 1 Western blot analysis was utilised for analysis of NOX5 and Actin protein expression on the total cell lysate. Results: The pre-treatment of Mo-DC with Tofacinitib inhibited Mo-DC differentiation in RA and PsA patients, as shown by reduced CD209 surface marker expression, and a mirrored increase of CD14 marker. The decreased ability of monocyte to differentiate into dendritic cells was translated into a function impairment of phagocytic ability, as observed by the decreased uptake of both DQ TM Ovalbumin (receptor-mediated endocytosis) and Lucifer Yellow (micropinocytosis) PsA cells treated with Tofacinitib. Low phagocytosis was observed in RA patients.NOX5 has previously been shown to play a key role in Mo-DC differentiation, 2 therefore we sought to investigate whether Tofacinitib could exert is effect on Mo-DC development through modulating NOX5. NOX5 protein expression was significantly decreased in Mo-DC pre-treated with Tofacinitib in PsA, and to a lesser extend in RA patients. Conclusions: Together, these observations suggest a novel mechanism of action of Tofacinitib in RA and PsA, by inhibiting Mo-DC development, which may alter migration of DC to the joint and subsequent activation of the immune response. References: [1] Luque A, Cárdenas-Brito S, Olivar R, Aran J. Assessment of Human Dendritic Cell Antigen Uptake by Flow Cytometry—BIO-PROTOCOL. http://www.bio-protocol.org/e974 (accessed Jan 23, 2018). [2] Marzaioli V, Hurtado-Nedelec M, Pintard C, Tlili A, Marie J-C, Monteiro R, Gougerot-Pocidalo M-A, Dang PM-C, El-Benna J. NOX5 and p22phox are two novel regulators of human monocytic differentiation into dendritic cells. Blood2017. Disclosure of Interest: V. Marzaioli Grant/research support from: Project funded by Pfizer, M. Canavan: None declared, S. Wade: None declared, C. Low: None declared, D. Veale: None declared, U. Fearon: None declared